Statistical aperture-based modeling of viscosity-influenced capillary pressure in rough fractures: The role of capillary number in invasion and hysteresis - Hao Feng; Zhechao Wang; Liping Qiao; Jingyi Ma (Advances in Water Resources, 2026)

Distribution of soil organic carbon in root zones at different distances from the maize basal stem axis and its response to organic materials - Kaixuan Wang; Sen Dou; Baozhao Feng; Boyan Zhang; Yuhan Xia; Dilimulati Yalihong; Yue Gu; Jingmin Yang (Journal of Soils and Sediments, 2026)

Effects of disconnected fluid interfaces on pressure drops for liquid-liquid-gas three-phase flow in porous media - Jiafan Guo; Zhechao Wang; Liping Qiao; Hao Feng (Advances in Water Resources, 2025)

Current Progress of the Long‐Term Preservation for Fish Embryos, Female Reproductive Cells, and Tissues - Wei Qin; Jiaji Pan; Jun Xiao; Hao Feng (Reviews in Aquaculture, 2025)
Cryopreservation is an effective technique to preserve biomaterials for a very long time period. The long‐term preservation techniques benefit the rapid development of the aquaculture industry, such as optimizing the breeding schemes. Currently, many cryopreservation attempts have been conducted on fish embryos and gametes. The cryopreservation of fish sperms is the most successful among these studies due to the simple structure of sperms. However, the cryopreservation of female gametes is developing at a much slower pace. In this work, the techniques and progress related to the cryopreservation of fish embryos, blastomeres, oocytes, testicular tissue, ovarian tissues, and primordial germ cells (PGCs) are introduced. This review first discusses the cryoprotective agents (CPAs) used in the cryopreservation or vitrification of fish embryos and gametes. Then we summarize advanced techniques including the pretreatment, rewarming methods, removal of CPAs, and assessment methods, followed by introducing the preservation results. In the end, some suggestions are raised for the future development of fish embryos, germ cells, and gonadal tissues.

The role of phase interference in steady-state two-phase flow in porous media - Jiafan Guo; Zhechao Wang; Liping Qiao; Hao Feng (Advances in Water Resources, 2025)

A hybrid CNN-transformer surrogate model for the multi-objective robust optimization of geological carbon sequestration - Zhao Feng; Bicheng Yan; Xianda Shen; Fengshou Zhang; Zeeshan Tariq; Weiquan Ouyang; Zhilei Han (Advances in Water Resources, 2025)